2010
DOI: 10.1055/s-0030-1267949
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Reduces PGE2Levels and Induces Recovery from Steatosis in Tumor-bearing Rats

Abstract: The effects of endurance training on PGE (2) levels and upon the maximal activity of hepatic carnitine palmitoyltransferase (CPT) system were studied in rats bearing the Walker 256 carciosarcoma. Animals were randomly assigned to a sedentary control (SC), sedentary tumor-bearing (ST), exercised control (EC), and as an exercised tumor-bearing (ET) group. Trained rats ran on a treadmill (60% VO (2) max) for 60 min/day, 5 days/week, for 8 weeks. We examined the mRNA expression (RT-PCR) and maximal activity (radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
2
11
0
11
Order By: Relevance
“…Corroborating our suggestion, PGE2 decreased CPT1 expression in isolated hepatocytes and the PGE2-dependent repression of CPT1 resulted in inhibition of mitochondrial β-oxidation and triacylglycerol accumulation in hepatocytes [35]. In addition, the exercise training normalized the increased level of PGE2 in the liver of Walker-256 tumor-bearing rats, restored the decreased activity of CPT1 and CPT2 and prevented hepatic steatosis [34]. Moreover, treatment with PGE2 or PGE2 receptor agonist increased the triacylglycerol in the liver [36].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Corroborating our suggestion, PGE2 decreased CPT1 expression in isolated hepatocytes and the PGE2-dependent repression of CPT1 resulted in inhibition of mitochondrial β-oxidation and triacylglycerol accumulation in hepatocytes [35]. In addition, the exercise training normalized the increased level of PGE2 in the liver of Walker-256 tumor-bearing rats, restored the decreased activity of CPT1 and CPT2 and prevented hepatic steatosis [34]. Moreover, treatment with PGE2 or PGE2 receptor agonist increased the triacylglycerol in the liver [36].…”
Section: Discussionsupporting
confidence: 68%
“…5B) and the decreased CPT1 expression in the liver of tumor-bearing rats (Fig. 6), suggesting a role of PGE2, which is increased in the liver [34] and blood [15,34] of Walker-256 tumor-bearing rats, in the inhibition of CPT1. Corroborating our suggestion, PGE2 decreased CPT1 expression in isolated hepatocytes and the PGE2-dependent repression of CPT1 resulted in inhibition of mitochondrial β-oxidation and triacylglycerol accumulation in hepatocytes [35].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, L-carnitine supplementation may protect hepatocytes of tumour-bearing rats from oxidative damage, since free fatty acids are able to produce damage on cell and mitochondrial surfaces (Bremer 1981). In addition, we have recently published a study in which we show that increased CPT activity is found in association with reduction in the enhancement in liver prostaglandin E2 content which is related with cachexia (Lira et al 2010). Roy et al (2009) found decreased PGE2 production by Caco-2 cells following treatment with carnitine.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, exercise could reduce the inflammation of the stomach of epithelium, as it has been previously proposed in other chronic inflammatory digestive disorders [2]. In the same line, the concentration of prostaglandin E 2 , a marker of inflammation that has been associated with gastric cancer risk [17], could be reduced due to the performance of endurance exercise [34]. Regarding the systemic effects, the evidence is based on the influence that the exercise performance seems to have on the immune system, mainly by improving its innate and acquired immune responses when recognising and eliminating cancerous cells [24].…”
Section: Introductionmentioning
confidence: 83%